Optimalisasi Kewenangan Kejaksaan Dalam Penghentian Penuntutan Perkara Perpajakan Melalui Denda Damai - Rahmattullah (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2024)
The settlement of tax crimes through the payment of a composition fine is essentially a case settlement in accordance with the principle of swift, simple, and low-cost justice, which also contributes to the optimization of state revenue. The Attorney General has the authority to approve a composition fine as a manifestation of the principle of opportunity in prosecuting economic crimes, including tax, customs, excise, and other economic crimes. Based on research, there is still a lack of harmony in the laws and regulations and implementation provisions regarding the settlement of tax crimes using composition fines carried out by the Prosecutor's Office. Therefore, it needs to immediately prepare implementing regulations regarding the application of composition fines in handling tax crime cases to harmonize the provisions contained in the Law on Harmonization of Tax Regulations and the Attorney General's Law related to the legitimacy of the Attorney General's authority to use this settlement.